Fast-scan terahertz time domain spectrometer based on laser repetition frequency modulation - Furuya, Takashi (Animo Repository, 2013)
We propose a high-speed scanning terahertz (THz) time-domain spectrometer (TDS) based on optical sampling by repetition frequency modulation (OSREFM) using a repetition-frequency-tunable femtosecond fiber laser. Repetition frequency modulation is controlled by a highly stabilized external sweep generator. The fast scan of the time-delay between the pump and probe pulses is similar to an optical sampling with cavity tuning (OSCAT) THz-TDS system. However, the advantage of this technique is that it does not require physically moving components and uses only one laser system having an electronically modulated repetition rate. The time window and scanning time of this system depend on the modulation frequency range and the sweeping speed of the laser. In this study, we demonstrate the acquisition of a ∼300 ps-window THz time waveform within 3 ms at a scan rate of 333 Hz.